2023
DOI: 10.1080/0886022x.2023.2292152
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in critical COVID-19 patients: usefulness of urinary biomarkers and kidney proximal tubulopathy

Romaric Larcher,
Anne-Sophie Bargnoux,
Stephanie Badiou
et al.

Abstract: Tubular injury is the main cause of acute kidney injury (AKI) in critically ill COVID-19 patients. Proximal tubular dysfunction (PTD) and changes in urinary biomarkers, such as NGAL, TIMP-2, and IGFBP7 product ([TIMP-2]•[IGFBP7]), could precede AKI. We conducted a prospective cohort study from 2020/03/09 to 2020/05/03, which consecutively included all COVID-19 patients who had at least one urinalysis, to assess the incidence of PTD and AKI, and the effectiveness of PTD, NGAL, and [TIMP-2]•[IGFBP7] in AKI and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Consistent with previous studies, patients with no AKI diagnosis had the highest transition rates to stage 1 AKI within the first week during the whole intensive care unit stay [ 39 ]. The incidence rate of AKI in patients with severe COVID-19 ranges from 41% to 62% [ 6 8 ], and most cases are classified as transient AKI that rapidly develops within the first week after SARS-CoV-2 infection [ 40 , 41 ]. Furthermore, we observed that mild COVID-19 infection had no significant influence on the risk of subsequent acute kidney disorder over the 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with previous studies, patients with no AKI diagnosis had the highest transition rates to stage 1 AKI within the first week during the whole intensive care unit stay [ 39 ]. The incidence rate of AKI in patients with severe COVID-19 ranges from 41% to 62% [ 6 8 ], and most cases are classified as transient AKI that rapidly develops within the first week after SARS-CoV-2 infection [ 40 , 41 ]. Furthermore, we observed that mild COVID-19 infection had no significant influence on the risk of subsequent acute kidney disorder over the 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with COVID-19, kidney involvement is common. The incidence rate of acute kidney injury (AKI) can reach 41% to 62% [ 6 9 ] in patients with COVID-19. Despite the high incidence of AKI, research has revealed that the majority of patients can recover within the first week (the median number of days to recover from AKI is 6) following infection [ 10 ].…”
Section: Introductionmentioning
confidence: 99%